(untitled) (Education in the 21st Century, 2023)
In the general system of raising children with visual impairments, including physical education, the role of the family is immeasurably increasing. At the same time, it is known that deep and partial visual impairments of a child greatly complicate and make it difficult to organize and conduct health-improving, strengthening, corrective-developing and many other activities in a family environment. Therefore, the correct and effective formulation of this work largely depends on the level of awareness of parents raising a blind and visually impaired child in matters of their physical education. The scientific and methodological literature emphasizes the role and importance of the family in the upbringing, education and development of children with visual impairment, the level of awareness of parents in these matters. At the same time, in the special literature and in practice, the problem of the formation and development of the level of awareness of parents of children with visual impairment in physical education does not pay due attention to them. Thus, the results of the study state that, on the one hand, the interviewed parents understand the importance of organizing and conducting physical education of these children in a family environment, but on the other hand, according to their frank admission, the vast majority of them do not have the appropriate knowledge and level of awareness in these matters. While the solution of this problem, the timely formation and development of parents’ awareness of the issues of physical education of children with visual impairment is very important for the full and comprehensive development of these children. In the article, based on the presented material, a theoretical analysis of the results is carried out, conclusions and practical recommendations are made.